Performance Analysis of District Office Employees East Jambe Bay Karawang District - Syari, Wulan; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2024)
Performance in an organization or government agency can be determined by the effectiveness of its employees'performance. Good employee performance can make it easier for an organization to achieves its goals. Apart from that, important for every organization to evaluate employee performance periodically to identify strengths and weaknesses, and to improve their performance. This research aims to analyze employee performance at the Teluk Jambe Timur District collected through interviews and observation. Next, it is analyzed to evaluate performance  inducators productivity, service quality, responsiviness and responsibility. In this research, the informants consisted of the sub-district head, sub-district secretary, staff and the community. The research results show the importance of developing system anad technology, expanding employee training and adjustment, improving the quality  of public service, regular monitoring and evaluation, as well as increasung employee responsiveness and responsibility as an effort to increase the effectiveness and efficiency of services to the comunity. The implication of this research is the need for concrete action to improve employee performance in order to achieve the expected results in public service.